Solution Processed NiOx as a Hole Transporting Layer for Inverted Perovskite Solar Cells - Ramos, André Morujo (2022)
The present thesis aims to contribute to fight the well known environmental emergency that our society is facing. To do so, this work has developed an emerging thin-film photovoltaic technology based in perovskite solar cells (PSCs), being mainly focused on the optimization of the hole transport layer (HTL) used as a p-contact of the devices. For that, in view of the promising propeties of Nickel Oxide (NiOx) as HTL material, four different types of films have been investigated and compared: undoped NiOx; magensium-doped NiOx; cobalt-doped NiOx and co-doped (with both magnesium and cobalt) NiOx. The properties of the developed NiOx and perovskite films were assessed by several characterization tools: UV-Vis-NIR Spectrometry, Photoluminescence spectrometry, AFM, SEM and GIXRD. In addition, the perovskite layer was also analysed with optical and materials characterization methods. The overarching performance of the developed NiOx based HTLs was then tested in real PSC devices contructed with the layer structure: ITO/NiOx/Perovskite/PCBM/BCP/Ag. The best results attained in this study correspond to a power conversion efficiency (PCE) of 9.49 %, an open circuit voltage (VOC) of 0.87 V, a fill factor (FF) of 0.57 and short-circuit current density (JSC) of 19.11 mA/cm2, obtained by a light soaked PSC with a cobalt-doped NiOx HTL. This is chiefly attributed to the less radiative recombination of the charge carriers in the perovskite layer deposited over such novel HTL material investigated in this thesis.